(untitled) (Research, Society and Development, 2021)
Objective: To present scientific evidence based on narrative review, following the PRISMA Protocol on auditory, dysphagic and language disorders in patients with Treacher Collins Syndrome. Methodology: The search for articles was carried out in the Lilacs, Pubmed, Science Direct, Scielo and Scopus databases, there was no restriction on location and language, the evaluated period consisted of 2015 to 2020. In the article selection process a combination based on Medical Subject Heading Terms (MeSH) was used. Four studies that scored ≥ 6 points according to the qualitative score protocol proposed by Pithon et al. (2015). Results: Patients affected by Treacher Collins syndrome may present complications in the upper airways, micrognathia, anatomical changes in the outer ear, dentition and temporomandibular joint. Conclusion: The syndromic characteristics of mandibulofacial dysostosis directly affect the hearing, speech, voice, swallowing and breathing of patients, and these are the particularities that make speech therapy in the multidisciplinary team extremely important for the prognosis and maintenance of the quality of life of patients affected by the syndrome Treacher Collins.